Hepatitis c virus infection and risk of venous thromboembolism: A systematic review and meta-analysis - Karn Wijarnpreecha (2018)
© 2017, Fundacion Clinica Medica Sur. All rights reserved. Background/Objectives. Hepatitis C virus (HCV) infection is one of the leading causes of cirrhosis. As a result of chronic inflammatory response to the virus, HCV-infected patients may be at a higher risk of venous thromboembolism (VTE). However, the data on this association is unclear. This systematic review and meta-analysis was conducted with the aims to summarize all available evidence. Material and methods. A literature search was performed using MEDLINE and EMBASE from inception to April 2016. Studies that reported relative risks, odd ratios, or hazard ratios comparing the risk of VTE among HCV-infected patients vs. subjects without HCV infection were included. Pooled risk ratios (RR) and 95% confidence interval (CI) were calculated using a random- effect, generic inverse variance method. Results. Three studies met our eligibility criteria and were included in analysis. The pooled RR of VTE in HCV-infected patients vs. subjects without HCV infection was 1.38 (95% CI, 1.08-1.77, I2= 40%). Subgroup analysis showed that risk was increased for both pulmonary embolism (PE) and deep venous thrombosis (DVT) even though without adequate power to demonstrate statistical significance (Pooled RR of 1.34, 95% CI, 0.67-2.66 for PE and pooled RR 1.45, 95% CI, 0.93-2.77 for DVT). Conclusion. Our study demonstrated a significantly increased risk of VTE among HCV-infected patients. Further studies are required to clarify how this risk should be addressed in clinical practice.